P2Y12 receptor inhibition and effect of morphine in patients undergoing primary PCI for ST-segment elevation myocardial infarction - Silvain, Johanne; Storey, Robert F.; Cayla, Guillaume; Esteve, Jean-Baptiste; Dillinger, Jean-Guillaume; Rousseau, Hélène; Tsatsaris, Anne; Baradat, Caroline; Salhi, Néjoua; Hamm, Christian W.; Lapostolle, Frédéric; Lassen, Jens Flensted; Collet, Jean-Philippe; ten Berg, Jurrien M.; van ’t Hof, Arnoud W.; Montalescot, Gilles (Thrombosis and Haemostasis, 2016)
PRIVATE-ATLANTIC (P2Y12 Receptor Inhibition with VASP Testing using Elisa kit during the ATLANTIC study) is a pre-specified substudy of the randomised, double-blind ATLANTIC trial in patients with ST-segment elevation myocardial infarction, designed to help interpret the main trial results. The primary objective of ATLANTIC was to assess coronary reperfusion prior to percutaneous coronary intervention (PCI) with pre- vs in-hospital ticagrelor 180 mg loading dose (LD). PRIVATE-ATLANTIC assessed platelet inhibition in 37 patients by measurement of vasodilator-associated stimulated phosphoprotein (VASP) platelet reactivity index (PRI) and VerifyNow platelet reactivity units (PRU) before angiogram (T1), immediately after PCI (T2), 1 (T3), and 6 (T4) hours (h) after PCI, and before next study drug administration (T5). The median time difference between the two ticagrelor LD was 41 minutes. Platelet reactivity was unaffected at T1 when measured by VASP-PRI (89.8 vs 93.9% for pre- and in-hospital ticagrelor, respectively; p = 0.18) or PRU (239 vs 241; p = 0.82). Numerical differences were apparent at T2 and maximal at T3. Morphine administration significantly delayed onset of platelet inhibition at T3 (VASP-PRI 78.2 vs 23.4% without morphine; p = 0.0116) and T4 (33.1 vs 11.0%; p = 0.0057). In conclusion, platelet inhibition in ATLANTIC was unaffected by pre-hospital ticagrelor administration at the time of initial angiogram due to the short transfer delay. The maximum difference in platelet inhibition was detected 1 h after PCI (T3). Morphine administration was associated with delayed onset of action of ticagrelor and appeared more important than timing of ticagrelor administration.
Keywords: Ticagrelor; platelet reactivity; morphine; STEMI; PCI